2023
DOI: 10.3390/vetsci10120683
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Based Technologies for the Evaluation of Testicles in the Dog: Keystones and Breakthroughs

Claudia Bracco,
Alessia Gloria,
Alberto Contri

Abstract: Ultrasonography is a valuable diagnostic tool extensively used in the andrology of human and domestic animals, including dogs. This review aims to provide an overview of various technologies based on ultrasound, from the basic B-Mode ultrasonography to the more recent advancements, such as contrast-enhanced ultrasonography (CEUS) and ultrasound elastography (UEl), all of which are utilized in the evaluation of canine testicles. The review outlines the principles behind each of these technologies and discusses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 173 publications
0
4
1
Order By: Relevance
“…Although correlations between semen parameters and prostatic and testicular volumes were previously reported (45)(46)(47), in our study there were no correlations between testicular volume and total sperm count, between testicular volume and sperm motility, or between prostatic volume and total sperm count. However, this discrepancy could be due to the limited number of dogs evaluated, that could have affected the power of the statistical analysis.…”
Section: Discussioncontrasting
confidence: 90%
“…Although correlations between semen parameters and prostatic and testicular volumes were previously reported (45)(46)(47), in our study there were no correlations between testicular volume and total sperm count, between testicular volume and sperm motility, or between prostatic volume and total sperm count. However, this discrepancy could be due to the limited number of dogs evaluated, that could have affected the power of the statistical analysis.…”
Section: Discussioncontrasting
confidence: 90%
“…According to Evans et al [ 3 ], the typical size dimensions of a mature testis are around 3 cm (major axis) to 2 cm (minor axis) in an 11 kg dog. However, the significant variation in canine body weight across breeds leads to a wide range of testicular sizes within this species [ 1 ]. For the Beagle breed, Gouletsou et al [ 10 ] found a mean volume of 9.5 cm 3 , whilst in a later study the same research group [ 41 ] reported a mean testicular volume of 8.3 cm 3 , with both findings in concordance with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonographic (US) imaging is a valuable diagnostic technique, widely employed in the study of the male reproductive system in humans and domestic animals [ 1 ]. It is easy to use, non-invasive, quick to perform, and less costly compared to other imaging techniques like magnetic resonance or computed tomography [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of CEUS for the evaluation of ovarian activity [ 28 ] and pregnancy [ 29 , 30 ], but also during pyometra [ 31 , 32 ], has been described in the bitch. For male dogs, there are several studies on both healthy [ 33 ] and pathological testes [ 34 , 35 , 36 ]; furthermore, some studies have been published on the prostate in healthy [ 37 , 38 , 39 ], neutered [ 40 ], and pathological animals [ 22 , 37 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%